Protótipos de filtros para água poluida usada para irrigação de hortaliças e frutiferas - Dematte, J. B I; Rodrigues, N. S.; Saito, S. M T; Tornisielo, V. L. (My University, 1987)
Prototypes A (bidin + broken stones + gravel stones + gross sand + activated coal) and B (bidin + broken stones + gravel stones + gross sand) under hydraulic charge of 35 cm presented outlets that, when extrapolated for larger filters, are sufficient to supply small and medium irrigation projects for vegetables and fruits. (bidin = Rhodia polyester for drainage). Under a charge of 35 cm, filtrate of both prototypes presented a reduction of fecal coliforms, being this reduction higher for A prototypes, but, even in this case, the coliform quantities were superior to the legal limit. Under a decrease of the biochemical oxygen demand an increase of the available oxygen rate; pH and hardness did not present significant changes.
Prototypes of filters for polluted water used for vegetable and fruit irrigation
Keywords: surface water; filtration; fruit; higher plant; land irrigation; vegetable; water treatment